National Financial Inclusion Strategy for Fighting Against Poverty and Enhancing Sustainable Economic Development in Albania (European Journal of Marketing and Economics, 2018)
This paper presents the issues that Albania is facing related to financial inclusion and the recommendations to be taken in consideration based on results of my qualitative and quantitative research over public reports, surveys and interviews. Based on the analyses of interviews for this paper with undergraduate students of economic faculties all around Albania, the results show that: a) about 62 percent of interviewees do not have knowledge for financial products such as mortgages, overdrafts, online banking, money transfer; b) about 94 percent of interviewees do not have knowledge for voluntary insurance products, investment pensions funds, investment funds, corporate bonds and equity investments; c) about 61 percent of interviewees do not know the role of BoA and AFSA as regulatory and supervisory authorities of financial markets in Albania; etc. Albania needs a national financial inclusion strategy for fighting against poverty and enhancing sustainable economic development of the country. This will contribute to achieve the enabling of the easy access and reasonable cost to a whole range of financial services - not just credit but also savings and payments - for individuals (regardless: the low level of income, gender, age, very young or very old, location, rural or urban, etc.) and businesses (regardless if they are: natural or legal person, small or large, with activities in agriculture or commerce, in the village or town, etc.). The financial education is key to understand what you sign when you invest. In Albania the level of financial education is very low which affects the financial decisions of adults, their life and sustainability of Albanian financial markets. Implementing obligatory financial education programs for each target group reduce social effects and intermediaries financial risks, increase healthy consumption and develop stable financial markets. Recommendations of this paper demand the involvement of the Albanian Government, regulatory authorities and other stakeholders for setting up a dedicated public structure as responsible for implementing asap measures for each targeted segment. According to World Bank, access to financial services made possible thanks to reforms. Albanian authorities (MoFE, MoESY, BoA, AFSA, ACA) must amend the legal and regulatory framework approaching EU Directives, OECD principles and best practices to enable competition not concentration, transparency, access to finance for vulnerable segments and quality financial services. By the other side, these authorities should supervise and take care without allowing shadow banking and other financial intermediaries not subject to any regulatory oversight, which is becoming a growing concern for supervisory authorities worldwide and mainly for developing countries.
Keywords: financial inclusion, financial education, consumers, businesses, regulatory authorities, financial intermediaries